Pengaruh Terapi Latihan pada Kondisi Pasca Section Caesarea dan Metode Wanita di RS PKU Muhammadiyah Karanganyar: Case Report - Tsania Khoirun Nisa; Wahyuni Wahyuni; Sudarmi Sudarmi (Journal of Educational Innovation and Public Health, 2026)
Post section caesarea (SC) and method of operative female sterilization (MOW) are surgical procedures that may cause various problems, such as pain, limited mobility, decreased muscle strength, and risk of postoperative complications. Physiotherapy management through exercise therapy is an important intervention to accelerate the recovery process. Objective this study aimed to determine the effectiveness of exercise therapy in improving the functional condition of patients post SC and MOW in Annisa Ward 32 A at PKU Muhammadiyah Karanganyar Hospital. Method: used was a case report on a 33-year-old female patient following SC and MOW procedures. The physiotherapy interventions included deep breathing exercises, active range of motion exercises of the extremities, light abdominal muscle contractions, gradual early mobilization, as well as breast massage and oxytocin stimulation. The results showed a reduction in pain from a scale of 4–5 to 2–3 based on the Numeric Rating Scale (NRS), improvement in mobility such as independent position changes, and increased activity tolerance, including sitting and walking with minimal assistance. In addition, the patient showed increased confidence in performing daily functional activities. Conclusion: exercise therapy has a positive effect on improving mobility, reducing pain, and accelerating functional recovery in post SC and MOW patients. Therefore, exercise therapy is recommended as an essential component of postoperative physiotherapy management to improve patients' quality of life.